Chemical injury caused by acute alendronic acid aspiration. (30th April 2014) - Ottaway, Zoe Victoria; Hammond, Cara; Merritt, Simon
Abstract : A 79-year-old woman was prescribed bisphosphonates 3 years ago for osteoporosis. At the time of first prescription, she received counselling directions on how to take her medication, which she stringently adhered to. However, she accidentally aspirated an alendronic acid tablet and subsequently developed respiratory tract symptoms. An emergency bronchoscopy was performed. We describe the marked bronchoscopic changes following aspiration of alendronic acid.